Growth of silver nanoparticles on unpolished silicon substrate by used of microwave-assisted technique to enhance the Raman spectrum of glucose. Issue 1 (1st May 2022) - Isnaeni,; Yudasari, Nurfina; Hidayah, Affi Nur
Abstract: Silver nanoparticle is useful metallic nanoparticle due to plasmonic property. One of the most important application of silver nanoparticle is enhancing Raman spectrum using so-called surface-enhanced Raman spectroscopy (SERS). Mostly, researchers synthesize colloidal silver nanoparticles and deposite on substrate to form SERS substrates. In this work, we simplified the synthesis of SERS substrate by use of microwave. We have successfully grown silver nanoparticles on unpolished silicon substrate using single step microwave-assisted technique. The unpolished silicon substrate has micro-size chambers that are useful for Raman measurement. The silver nanoparticles on silicon substrate were approximately 88 nm in diameter. Our experiment using corn syrup revealed that our SERS substrate enhance Raman peaks spectra of glucose and galactose by more than 16 times.